TINDAK TUTUR ILOKUSI DALAM NOVEL HOME SWEET LOAN KARYA ALMIRA BASTARI - Ramadani, Suci; Mayong, Mayong; Asri, Aswati (Neologia: Jurnal Bahasa dan Sastra Indonesia, 2026)
This study aims to describe the forms and functions of illocutionary speech acts found in the dialogues of Almira Bastari’s novel Home Sweet Loan. The objectives of the study are to describe the forms of illocutionary speech acts in Almira Bastari’s novel Home Sweet Loan, and to describe the functions of illocutionary speech acts in Almira Bastari’s novel Home Sweet Loan. This study employs a qualitative descriptive method, with data sourced from the dialogues in Almira Bastari’s novel Home Sweet Loan. The data collection techniques used are reading, note-taking, and documentation. The results of this study indicate that five forms of illocutionary speech acts were identified in Almira Bastari’s novel Home Sweet Loan, namely assertive, directive, expressive, commissive, and declarative. Twenty functions of illocutionary acts were identified. Four functions of the assertive illocutionary act were found: stating, suggesting, complaining, and affirming. Eight functions of the directive illocutionary act were found: commanding, requesting, advising, recommending, prohibiting, asking, warning, and questioning. Five functions were identified in the expressive speech act category: expressing gratitude, offering congratulations, apologising, blaming, and praising. Twenty functions were identified in the commissive speech act category: offering something and refusing. One function was identified in the declarative speech act category: resigning oneself.